High-entropy FeCoNiMnCu alloy coating on ferritic stainless steel for solid oxide fuel cell interconnects - Zhao, Qingqing; Geng, Shujiang; Zhang, Yu; Chen, Gang; Zhu, Shenglong; Wang, Fuhui (Journal of alloys and compounds, 2022)
A high-entropy alloy coating of FeCoNiMnCu was prepared on SUS 430 steel via magnetron sputtering for solid oxide fuel cell (SOFC) interconnects application. The coated steels were subject to thermal exposure in air at 800 °C for up to 10 weeks. Phase constituents, microstructure and area specific resistance (ASR) of the coated steel before and after the oxidation testing were investigated. Results indicated the alloy coating was thermally converted into a high-entropy spinel coating of (Fe,Co,Ni,Mn,Cu)3O4 after oxidation and a protective Cr2O3 layer was formed at the steel/coating interface. The (Fe,Co,Ni,Mn,Cu)3O4 spinel coating effectively suppressed growth of Cr2O3 layer and outward diffusion of Cr during the long term exposure. Scale ASR of the coated steel was as low as 6.59 mΩ·cm2 at 800 °C after 10 weeks. It indicates that (Fe,Co,Ni,Mn,Cu)3O4 is a promising coating material for SOFC metallic interconnects. •A high-entropy alloy coating of FeCoNiMnCu is sputtered on SUS430 steel.•The coating is thermally converted into a high-entropy (Fe,Co,Ni,Mn,Cu)3O4 spinel.•The spinel coating effectively suppresses growth of Cr2O3 and out-diffusion of Cr.•Area specific resistance of coated steel is sufficiently low after long term exposure.